Ionisk selvsamling med ponceau 4R og benzyldimethylhexadecyl- - Anker, Andy Sode; Özdemir, Burak; Schlosser, Rasmus Dalsgaard; Sandager, Stephanie (UCPH NanoScience - a student research journal, 2017)
N/A